Structural synthesis of electronic system and optimization of control process - Савчук, Н. Н. (Proceedings of National Aviation University (archive), 2000)
Considered are the problematic question of structural synthesis of electronic system of control of dynamic processes based on the methods of diacoptic and multisequencing. Proposed is the structure of electronic system of control process optimization with reciprocating motion